2023
DOI: 10.3389/fneur.2023.1142424
|View full text |Cite
|
Sign up to set email alerts
|

Stroke territory and atherosclerosis in ischemic stroke patients with a history of migraine with aura

Abstract: IntroductionThe mechanisms subtending the increased stroke risk in migraine with aura (MA) are not fully understood. Our study aims to evaluate if the clinical profile in stroke patients with MA differentiates from those without MA.MethodsWe retrieved the prospective registered electronic clinical dossiers of adult patients younger than 60 years with acute ischemic stroke admitted in four hospitals between January 2016 and June 2022. Patients were classified by the history of MA (MA+ and MA–).ResultsWe identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A recent multicenter cohort study showed that among all 851 patients with migrainous cerebral infarction, MA patients were more frequently women and younger in age. 41 It was also shown that for young men, migraine increased the risk of ischemic stroke similarly to that of women. 42 The risk of stroke in elderly migraineurs has also been explored, with conflicting results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent multicenter cohort study showed that among all 851 patients with migrainous cerebral infarction, MA patients were more frequently women and younger in age. 41 It was also shown that for young men, migraine increased the risk of ischemic stroke similarly to that of women. 42 The risk of stroke in elderly migraineurs has also been explored, with conflicting results.…”
Section: Discussionmentioning
confidence: 98%
“… 53 Stroke patients with MA are also less likely to have hypertension, diabetes, and dyslipidemia, which implies that migraine-induced risk of stroke is independent. 41 , 55 , 56 However, dyslipidemia and smoking increase the Framingham risk score in migraineurs. 53 Notably, there are two conditions in which traditional vascular risk factors still play an important role in stroke attacks, one in patients with CADASIL and the other in pregnant patients with migraine headaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Hyperalgesia in migraine is underlined by several aspects, including neurons-glia crosstalk and disturbing the balance of the neurotransmitters in the nervous system by microglia, astrocytes, and satellite cells can induce migraine headaches; 40 however, not all aspects of the involvement of microglia in migraine are clear. Some studies report that migraine, especially migraine with aura, may be a risk factor for ischemic stroke (IS); 41,42 however, most of these studies were performed on elderly cohorts, in which cardiovascular burden might be so high that it could suppress the difference in the risk resulted from migraine status. 43 This may be the reason that certain studies detected a tendency only without a statistical significance.…”
Section: Neuron S' Interpl Ay With MI Crog Lia In Mig R Aine Pathog E...mentioning
confidence: 99%
“…Some studies report that migraine, especially migraine with aura, may be a risk factor for ischemic stroke (IS); 41,42 however, most of these studies were performed on elderly cohorts, in which cardiovascular burden might be so high that it could suppress the difference in the risk resulted from migraine status 43 . This may be the reason that certain studies detected a tendency only without a statistical significance 44 .…”
Section: Neurons’ Interplay With Microglia In Migraine Pathogenesismentioning
confidence: 99%